Dendritic cells continue to capture and present antigens after maturation in vivo - Drutman, Scott B. (2010)
Dendritic cell (DC) maturation is critical for the regulation of T-cell responses. The down regulation of endocytosis upon maturation is considered a key adaptation that dissociates prior antigen capture by DCs from subsequent T-cell engagement. In order to study the dynamics of antigen capture and presentation in situ, we studied the capacity for antigen uptake by DCs matured in their natural tissue environment. We found that after maturation in vivo mouse DCs retained a robust capacity to capture soluble antigens. Furthermore, antigens internalized by mature DC were efficiently presented on MHC-class II and cross-presented on MHC-class I. These results suggest that under inflammatory conditions mature DC may contribute to T-cell stimulation without exclusively relying on prior exposure to antigens as immature DC precursors.